Use of Direct Oral Anticoagulants in Patients with Cancer: Practical Considerations for the Management of Patients with Nausea or Vomiting. (12th April 2018) - Riess, Hanno; Ay, Cihan; Bauersachs, Rupert; Becattini, Cecilia; Beyer‐Westendorf, Jan; Cajfinger, Francis; Chau, Ian; Cohen, Alexander T.; Khorana, Alok A.; Maraveyas, Anthony; Renni, Marcos; Young, Annie M.
Abstract : : Direct oral anticoagulants (DOACs) have proven efficacy and safety and are approved for use in the prevention and treatment of thromboembolic events in patients with venous thromboembolism (VTE) and those with atrial fibrillation (AF). There is no clear guidance on the use of DOACs in the significant proportion of these patients who have or will develop concomitant cancer. The occurrence of nausea and vomiting in these patients, despite implementation of guideline‐recommended antiemetic strategies, is a particular concern because it may affect oral drug intake and consequently outcomes with anticoagulation therapy. Here, we review recent data on the incidence and management of cancer‐associated nausea and vomiting and the current evidence and guidance relating to the use of DOACs in patients with cancer. On the basis of this evidence, an international working group of experts in the fields of cancer‐associated thrombosis/hemostasis, hematology, and oncology discussed key issues related to the use of DOACs in patients with VTE or AF and cancer who are at risk of nausea and vomiting and developed some consensus recommendations. We present these consensus recommendations, which outline strategies for the use and management of anticoagulants, including DOACs, in patients with VTE or AF and cancer for whom oral drug intake may pose challenges. Guidance is provided on managing patients with gastrointestinal obstruction or nausea and vomiting that is caused by cancer treatments or other cancer‐related factors. The recommendations outlined in this review provide a useful reference for health care professionals and will help to improve the management of anticoagulation in patients with VTE or AF and cancer. Implications for Practice: Direct oral anticoagulants (DOACs) offer several advantages over traditional anticoagulants, including ease of administration and the lack of need for routine monitoring. However, the management of patients with an indication for anticoagulation and concomitant cancer, who are at high risk of thromboembolic events, presents several challenges for administering oral therapies, particularly with regard to the risk of nausea and vomiting. In the absence of robust data from randomized trials and specific guidelines, consensus recommendations were developed for healthcare professionals regarding the use of DOACs in patients with cancer, with a focus on the management of patients who are at risk of nausea and vomiting. Abstract : The consensus recommendations outlined in this review provide a useful reference for health care professionals and will help to improve the management of anticoagulation in patients with venous thromboembolism, atrial fibrillation, and cancer who are at risk of nausea and vomiting.